A dictated policy: cartoons and the 1936 strike in Palestine. Issue 1 (2nd January 2017) - Barnes, Jeffrey John
Abstract : Current scholarship emphasises the dominant role played by the Arab press in the general strike in Palestine in 1936. In spite of this, cartoons, a crucial feature of Filastin – the most widely circulated Arabic-language daily in the Mandate – have received little scholarly attention. The current paper seeks to correct this through examining editorial cartoons to demonstrate how they reflect Filastin's role in engendering sympathy toward and participation in the general strike among a broader audience than could be reach by the textual content of the paper. Cartoons contributed to the transformation of what it meant to be Palestinian in the context of the broader national struggle against Great Britain and Zionism by examining discourses of 'peoplehood' – i.e. intersecting and overlapping categories of identity – interrogating subjects such as gender, nation and class to mobilise disparate elements of Palestinian society against colonial intrusion.